A Comprehensive Approach to Dynamic Project Risk Management. Issue 2 (3rd April 2018) - Sols, Alberto
Abstract: A large percentage of projects suffer performance, cost, and/or schedule problems. There are many reasons why projects fail, including an inadequate approach to risk management. Inadequate approaches result when a comprehensive identification of risks is not performed at project commencement, when risk assessment fails to consider important aspects, when no subsequent follow-up is carried out for mitigation strategies adopted, when no further identification of risks during project execution is completed, or a combination of these occurs. A number of publications have dealt with different facets of risk management, but not in a comprehensive way. This article compiles the approaches applied and observed by the author based on 25 years of industry experience; these observations were synthesized and result in a procedure for dynamic risk management successfully applied to a number of projects. The use of a broad array of techniques is suggested to identify risks, which are then thoroughly analyzed. The assessment was performed using a comprehensive array of criteria. The complete set of criteria included essential ones such as aggregability factor, triggering factor, early warning, immediacy, and recoverability. The thorough assessment was done dynamically. The initial assessment enables the adoption of the most adequate mitigation strategies, which later on are dynamically validated. New risks are also detected and dealt with dynamically throughout project execution. The main contribution of this work is the synthesis of state-of-the-art knowledge into a state-of-the-practice procedure, which can be applied by engineering managers in all sectors and in all phases of project execution.